Modernisasi dan Perubahan Sosial dalam Lintasan Sejarah Islam - Syamsul Bakri (Universitas Darussalam Gontor, 2016)
This paper describes about the modernization of Islam in the history. Modernization is the inevitable cosmic necessity, so that the Islamic world is forced by history to be able to response and to adapt to the dynamics of modernity. As a real impact, the process has created intellectuals and activists of Islam that involve in the acts of social movements. They tried to face the challenges of the modernity. Islam is not moving in the empty space. However, Islam appears in the middle of the people who need answers to the modernity that increases progressively. This fact is clearly the starting point of the importance of the dynamic religious understanding. In this context, ijtihad will be the only way to keep the conservation doctrine, and at the same time is able to follow the rhythm of modernity. The role of thinkers and activists of Islamic reform is very significant in making products of ijtihad to bring the Muslims facing social change as a result of modernization. Islam is a spirit of change, and then it creates social change while still having roots of theology and Islamic traditions. The modernization which is born from the womb of Western civilization has awakened the Muslims to aware the importance of Islam as a part of the social system. Islam has a strength and a great potential to build the nation. Therefore, Muslims should be agents of change to have social mobility.